Integrated heat-insulating component and preparation method and application thereof

By using nano-silicon dioxide and other materials combinations and hydraulic molding technology, the heat spillover and complex production of thermal insulating parts of electric ceramic furnaces is solved, and the insulation parts with high efficiency, low cost and stable performance are achieved to meet modern electric ceramics Strict requirements for furnaces.

CN119118620BActive Publication Date: 2025-01-10FOSHAN KELINGSI TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411604501.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-10
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The heat-spreading components of existing electric ceramic furnaces have problems such as heat spillover, complex production processes, high costs and unstable performance. In particular, the split structure is prone to heat loss and displacement during assembly and use, affecting the heating efficiency and service life. .

Method used

Using nano-silicon dioxide, pseudo-thin aluminite, high-silicon-chopped fibers, titanium dioxide and magnesium aluminum silicate powder and other materials, the integrated disk insulation parts are prepared through hydraulic molding technology to ensure edge strength and electrical gaps, and simplify the Production process and improve thermal insulation performance.

Benefits of technology

It effectively reduces heat loss, improves thermal insulation efficiency and energy efficiency, reduces production costs, enhances the insulation performance and structural strength of the products, and meets the strict requirements of modern electric ceramic furnaces for thermal insulation components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses an integrated heat-insulating component and its preparation method and application, which belongs to the technical field of heat-insulating materials. The heat-insulating component is made of raw materials such as nano-silicon dioxide, pseudo-boehmite, high-silica chopped fibers, rutile titanium dioxide and magnesium aluminum silicate powder, which are mixed in a specific proportion and made by stirring, molding and die-casting processes. Compared with the prior art, the integrated heat-insulating component design of the present invention effectively reduces the heat overflow from the junction of the ring and pad of the heating plate, thereby reducing heat loss and improving heat insulation efficiency. The production of the integrated heat-insulating component eliminates the steps of assembling the traditional heat-insulating ring and heat-insulating pad separately, reduces the production process, helps to improve production efficiency and reduce production costs, and has good industrialization prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal insulation materials, and in particular to an integrated thermal insulation component and a preparation method and application thereof. Background Art

[0002] As a stove device that converts electrical energy into thermal energy by using the thermal effect of electric current, the efficiency and thermal insulation performance of the heating plate, the core component of the electric ceramic stove, play a vital role in the performance of the entire device. In the prior art, the thermal insulation component of the electric ceramic stove usually consists of an insulation ring and an insulation pad. In this split structure, the insulation ring is placed on the insulation pad during assembly.

[0003] However, this design has some defects that cannot be ignored. In the traditional split insulation component structure, the junction between the insulation ring and the insulation pad is prone to heat overflow, resulting in additional heat loss and reducing the thermal efficiency of the heating plate. The split components need to be produced and assembled separately, which not only increases the production process, but also increases manufacturing costs and time. The performance and service life of the heating plate may be affected by the displacement or deformation of the insulation components during assembly and use.

[0004] The purpose of the present invention is that Chinese invention patent CN114133258A discloses a mullite micro-nanoporous thermal insulation refractory material and a preparation method thereof. The thermal insulation refractory material is mainly made of base material, additives and water, and the preparation process is green, environmentally friendly, pollution-free, simple and easy to control. The main crystal phase of the thermal insulation refractory material is large-sized needle and columnar mullite. The product has a white or light yellow appearance, and the pore size distribution is between 0.006-200μm, with an average pore size of 0.1-19μm. The closed spherical micro-nano pore structure ensures that the product has better thermal insulation performance at lower volume density and high strength. By regulating the amount of each raw material and the process, the final thermal insulation refractory material can meet the requirements of low thermal conductivity and lightweight, and also has better mechanical properties. However, its thermal insulation, energy efficiency, insulation and strength are insufficient.

[0005] In order to solve these problems, the industry urgently needs a new type of thermal insulation component that can be integrally formed with the heating plate to effectively prevent heat overflow, while simplifying the production process, reducing costs, and improving product stability and durability. Summary of the invention

[0006] In view of the defects of the prior art, the present invention aims to provide a new type of heat-insulating component for the heating plate of an electric ceramic stove, which can be integrally pressed and formed, effectively reducing heat loss and simplifying the production process. At the same time, the present invention also aims to provide a method for preparing such a heat-insulating component, so that the heat-insulating component can fix the heating resistance wire while having sufficient edge strength and required height to ensure electrical clearance, thereby meeting the strict requirements of modern electric ceramic stoves on the performance of heat-insulating components.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0008] The preparation method of the integrated heat-insulating component comprises die-casting each raw material, wherein each raw material is prepared in the following weight percentage:

[0009] (1). Nano silicon dioxide 30-70%;

[0010] (2). Pseudo-boehmite 5-25%;

[0011] (3). High silica chopped fibers 1-10%;

[0012] (4). Titanium dioxide 3-15%;

[0013] (5). Magnesium aluminum silicate powder 5-20%.

[0014] The specific surface area of ​​the nano-silicon dioxide is 80-120 m 2 / g; the particle size of pseudo-boehmite is ≤50μm; the diameter of high-silica chopped fibers is 5-8μm, and the length is between 6±2mm; the titanium dioxide is rutile titanium dioxide, and the particle size of rutile titanium dioxide is 180-220μm; the mesh number of magnesium aluminum silicate powder is 1100-1300 mesh.

[0015] The preparation method of the integrated disc thermal insulation component is as follows: nano-silicon dioxide, pseudo-boehmite, high-silica chopped fibers, titanium dioxide, and magnesium aluminum silicate powder are weighed according to the formula ratio and added into a mixer in sequence, and stirred evenly at room temperature for 5-15 minutes to obtain a final mixed powder to be formed for the thermal insulation component; the mixed powder is put into a special forming mold for the thermal insulation component, and the mixed powder is die-cast into the thermal insulation component.

[0016] The die casting uses a 80T-250T hydraulic press to apply a pressure of 20MPa-120MPa and a time range of 1-10s to die-cast the mixed powder into a heat-insulating component. Hydraulic press model: YT-100S-00.

[0017] Preferably, the raw materials are formulated as follows by weight percentage:

[0018] (1). Nano silicon dioxide 30-60%;

[0019] (2). Pseudo-boehmite 5-25%;

[0020] (3). High silica chopped fibers 1-10%;

[0021] (4). Titanium dioxide 3-15%;

[0022] (5). Magnesium aluminum silicate powder 5-20%;

[0023] (6). Thermal insulation material 1-10%.

[0024] The preparation method of the thermal insulation material is as follows, in parts by weight:

[0025] S1, placing 0.3-0.5 parts of carbon aerogel in a vacuum dryer, and adding 0.4-0.6 parts of triacetoxyvinylsilane and 0.7-0.9 parts of 0.5-2 mol / L sodium hydroxide aqueous solution in the vacuum dryer, respectively, sealing and evacuating; placing the vacuum dryer in an insulated box at 160-180° C. for 5-10 hours to obtain pretreated carbon aerogel;

[0026] S2, mixing 8-12 parts of silicone sol, 5-7 parts of water and 3-5 parts of anhydrous ethanol and stirring for 1-3 hours to prepare polysiloxane sol;

[0027] S3, uniformly dispersing the pretreated carbon aerogel prepared in step S1 and 0.1-0.3 parts of alumina fiber in the polysiloxane sol prepared in step S2, stirring at 10-30 rpm at 60-80°C for 1-5 hours, then heating to 70-90°C, and heat preservation for 4-8 hours; heating to 1000-1500°C in a nitrogen atmosphere, heat preservation for 2-6 hours, and cooling to room temperature with the furnace to obtain a composite material;

[0028] S4. Place the composite material obtained in step S3 in a tubular furnace, heat it to 500-700°C in an air environment, and keep it warm for 4-6 hours. Then place it in a vacuum dryer, treat it with 0.4-0.6 parts of 1,8-bis(trichlorosilylethyl)hexafluorooctane at 60-80°C for 1-5 hours, and then dry it to obtain a thermal insulation material.

[0029] The siloxane sol is composed of vinyl trimethoxy silane and methacryloxypropyl methyl diethoxy silane in a mass ratio of 0.5-2:0.5-2.

[0030] Preferably, the preparation method of the integrated disc insulation component is as follows: nano-silica, pseudo-boehmite, high-silica chopped fibers, titanium dioxide, magnesium aluminum silicate powder, and insulation materials are weighed according to the formula ratio and added into a mixer in sequence, and stirred evenly at room temperature for 5-15 minutes to obtain the final mixed powder to be formed for the insulation component; the mixed powder is put into a special molding mold for the insulation component, and the mixed powder is die-cast into the insulation component.

[0031] Among the materials used, nano-silica is a nano-scale high-porosity, high-specific surface area, high-quality insulating and heat-insulating refractory material, which has a cost advantage over traditional fumed silica; high-purity pseudo-boehmite is an aluminum oxide crystal, whose crystal phase is formed in the synthesis of aluminum hydroxide. The crystal shape is a thin folded sheet, with the characteristics of high specific surface and large pore volume, non-toxic, tasteless, odorless, white powder (dry product), high crystal phase purity, good peptization performance, and strong adhesion. High-silica short-cut fiber is a high-purity glass fiber containing more than 95% SiO2, with high specific strength and refractoriness. Rutile titanium dioxide is a white powdery inorganic material with high purity, high refractive index, non-toxic and high temperature resistance, and stable chemical properties. It can be used in refractory materials to improve the product's life, thermal insulation and high temperature resistance, and at the same time improve the product's density. Magnesium aluminum silicate powder is a non-toxic and tasteless inorganic gel powder with high temperature stability and good thermal insulation, insulation and mechanical properties.

[0032] Therefore, it can be understood that the technical solution of the present invention adopts a thermal insulation material composition of nano-silicon dioxide, high-purity pseudo-boehmite, high-silica chopped fibers, titanium dioxide, and magnesium aluminum silicate powder to prepare thermal insulation components in a certain proportion. Since the materials used have low thermal conductivity, good insulation properties, and high density and strength, the thermal insulation pad prepared from the thermal insulation material composition has good temperature insulation, energy saving, insulation effects and excellent structural strength.

[0033] Further preferably, the present invention also provides a method for preparing a thermal insulation component, the method comprising the following steps:

[0034] First of all, the product is produced using hydraulic press equipment. The bottom mold is designed with the edge and the middle separated, and the edge can move up and down. When feeding, the edge mold slides down to the set position, so that more material can be put into the edge of the product; after the feeding is completed, the upper mold is pressed down to the set position, and the bottom mold rises to the set position; the upper mold returns to its position, and the bottom mold continues to rise to the set position to push the product out of the barrel; the product is taken out, and the production pressing work is completed.

[0035] It should be noted that the powder material of this formula has a suitable particle size, which meets the material volume compression ratio and mold design requirements, making product production feasible.

[0036] Secondly, weigh the corresponding weight of nano-silicon dioxide, pseudo-boehmite, high-silica chopped fibers, titanium dioxide, and magnesium aluminum silicate powder according to the weight ratio of the proposed formula, and then add them to the mixer in sequence, and stir at room temperature for 10-30 minutes until the mixture is uniform, to obtain a mixture to be formed for the thermal insulation component;

[0037] Third, the mixture of the heat insulation component to be molded is put into a specific molding mold for the heat insulation component, and the mixed powder is die-cast into the heat insulation component using a hydraulic press ranging from 80T to 250T at a pressure range of 20MPa to 120MPa and a time range of 1s to 10s. The model of the hydraulic press is YT-100S-00.

[0038] Since the selected thermal insulation material has excellent high temperature resistance and thermal insulation effect and high insulation performance and specific strength, the prepared thermal insulation component also has good fire-resistant thermal insulation effect and pressure-resistant insulation performance and sufficient strength.

[0039] The heat-insulating component obtained by the above formula and preparation method provided by the present invention is suitable for an integrally formed heating plate of an electric ceramic stove.

[0040] In the preparation method of the thermal insulation material, the functions of each substance are as follows:

[0041] Carbon aerogel accounts for a relatively small proportion in the thermal insulation component. As a highly efficient reinforcing material, it improves the overall mechanical strength and structural stability of the thermal insulation component. Due to its small addition amount, the presence of carbon aerogel does not have a negative impact on the insulation performance of the thermal insulation component. Instead, it helps to maintain the light weight of the material and the excellent thermal insulation effect. In the voltage resistance test, the insulation performance exhibited by the thermal insulation component of the present invention is less than 5mA, which is far below the safety standard limit, proving that even if it contains a trace amount of carbon aerogel, it will not significantly enhance the conductivity, ensuring the safety and reliability of the product.

[0042] Triacetoxyvinylsilane is a silane coupling agent, which may be used here for its reactivity to enhance the interfacial bonding of the composites by forming chemical bonds with carbon aerogel.

[0043] As an alkaline catalyst, aqueous sodium hydroxide solution may be used to promote the hydrolysis and condensation reaction of triacetoxyvinylsilane, thereby forming chemical bonds on the surface of carbon aerogel.

[0044] The siloxane sol is composed of vinyl trimethoxy silane and methacryloxypropyl methyl diethoxy silane, and serves as a matrix material to provide the main structure of the thermal insulation material.

[0045] As a part of the siloxane sol, vinyltrimethoxysilane provides a network structure of the siloxane matrix and helps to form a stable polymer matrix.

[0046] Methacryloxypropylmethyldiethoxysilane is also included as part of the siloxane sol, possibly to provide additional crosslinking points, increasing the mechanical strength and temperature resistance of the matrix.

[0047] Anhydrous ethanol is used as a solvent to help the silicone sol to be better mixed and dispersed.

[0048] Alumina fiber is used as a reinforcing material to improve the mechanical strength and wear resistance of the thermal insulation material.

[0049] Nitrogen atmosphere During high temperature treatment, nitrogen is used as a protective atmosphere to prevent the material from being oxidized at high temperatures.

[0050] 1,8-Bis(trichlorosilylethyl)hexafluorooctane as a surface treatment agent may be used to form a hydrophobic layer on the surface of the composite material to enhance the waterproof performance and service life of the thermal insulation material.

[0051] Tube furnaces are used to heat composite materials to high temperatures for thermal treatment to cure and sinter the materials.

[0052] The vacuum dryer is used to remove moisture and volatile components from the material at low temperature to ensure the dryness of the insulation material.

[0053] Through the synergistic effect of these substances, the prepared insulation material has good thermal insulation performance, mechanical strength and temperature resistance, and is suitable for high-performance insulation applications.

[0054] Compared with the prior art, it has the following beneficial effects:

[0055] 1) The one-piece heat-insulating component design of the present invention effectively reduces the heat spillage from the ring-pad joint of the heating plate, thereby reducing heat loss and improving heat insulation efficiency.

[0056] 2) Due to the improved thermal insulation performance of the integrated heat-insulating plate component prepared by the present invention, the heat energy of the heating plate can be used more effectively, reducing energy waste, thereby improving the overall energy efficiency.

[0057] 3) The production of the integrated heat-insulating component of the present invention eliminates the steps of separately assembling the traditional heat-insulating ring and the heat-insulating pad, reduces the production process, and helps to improve production efficiency and reduce production costs.

[0058] 4) The thermal insulation material composition of the present invention has excellent insulation performance and sufficient mechanical strength after a specific formulation and process treatment, thus ensuring the reliability and durability of the product during use. DETAILED DESCRIPTION

[0059] Main sources of substances:

[0060] Nano-silicon dioxide: particle size 50nm, the specific surface area of ​​nano-silicon dioxide is 80-120m 2 / g between;

[0061] Pseudo-boehmite: specific surface area (BET) ≥ 230m 2 / g, pore volume: 0.5-0.8cm 3 / g, pore size: 5-10nm, particle size ≤50μm;

[0062] The diameter of high-silica chopped fiber is 7μm, and the length is between 6±2mm. It is a high-temperature resistant inorganic fiber with a silica content higher than 96% and a softening point close to 1700℃. It can remain in good condition after long-term use at 900℃, working at 1450℃ for 10 minutes, and working at 1600℃ for 15 seconds.

[0063] Rutile titanium dioxide: particle size is 180-220μm, active ingredient content ≥93%, color: white;

[0064] Magnesium aluminum silicate powder: mesh size is 1250 mesh, pH value (5% aqueous solution): 9-10, water-soluble matter <1%, acid-soluble matter <1%, dispersion viscosity (5% solid content): 800-2000cps;

[0065] The diameter of the grid colloid particles of carbon aerogel is 5nm-30nm, the typical pore size is 60nm-100nm, and the porosity is greater than 75%;

[0066] Alumina fiber: compressive strength: 0.004Mpa, refractory temperature: 1600℃, fiber diameter: 3.2μm;

[0067] Vinyltrimethoxysilane: CAS No.: 2768-02-7;

[0068] Methacryloxypropylmethyldiethoxysilane: CAS No.: 65100-04-1;

[0069] 1,8-Bis(trichlorosilylethyl)hexafluorooctane: CAS No.: 445303-83-3;

[0070] Dimethyldimethoxysilane: CAS number: 1112-39-6;

[0071] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.

[0072] The design concept of the present invention is to solve the heat loss problem of the existing electric ceramic stove heating plate insulation component in the traditional split structure, and to achieve the one-piece molding of the insulation component by developing a new type of insulation material composition and its preparation method. Through the precise control of mold design and raw material ratio, the bottom material of the heating plate can fix the heating resistor wire, while the edge part enhances its structural strength, ensures the electrical gap and supports the heating plate structure. By accurately controlling the percentage of each component in the material formula and adopting a specific preparation process, the present invention not only improves the insulation effect and energy efficiency of the insulation component, but also simplifies the production process, reduces costs, improves production efficiency, and ensures the insulation performance and structural strength of the product, meeting the strict requirements of modern electric stoves on the performance of insulation components.

[0073] The technical scheme in the embodiment of the present invention will be described in detail below. It should be noted that the described embodiment is only a part of the process of the present invention rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0074] Example 1

[0075] The preparation method of the integrated tray heat insulation component is as follows:

[0076] The raw materials are formulated as follows by weight percentage:

[0077] (1). Nano silicon dioxide 50%;

[0078] (2). Pseudo-boehmite 20%;

[0079] (3). High silica chopped fibers 2%;

[0080] (4). Rutile titanium dioxide 5%;

[0081] (5). Magnesium aluminum silicate powder 23%;

[0082] Nano-silica, pseudo-boehmite, high-silica chopped fibers, rutile titanium dioxide, and magnesium aluminum silicate powder are weighed according to the formula ratio and added into a mixer in sequence, and stirred evenly at room temperature for 10 minutes to obtain the final mixed powder to be formed for the thermal insulation component; the mixed powder is put into a special forming mold for the thermal insulation component, and a 100T hydraulic press is used to apply a pressure of 100MPa, and the hydraulic press model is: YT-100S-00, to die-cast the mixed powder into the thermal insulation component.

[0083] Example 2

[0084] The preparation method of the integrated tray heat insulation component is as follows:

[0085] The raw materials are formulated as follows by weight percentage:

[0086] (1). Nano silicon dioxide 60%;

[0087] (2). Pseudo-boehmite 15%;

[0088] (3). High silica chopped fibers 5%;

[0089] (4). Rutile titanium dioxide 5%;

[0090] (5). Magnesium aluminum silicate powder 15%;

[0091] Nano-silica, pseudo-boehmite, high-silica chopped fibers, rutile titanium dioxide, and magnesium aluminum silicate powder are weighed according to the formula ratio and added into a mixer in sequence, and stirred evenly at room temperature for 10 minutes to obtain the final mixed powder to be formed for the thermal insulation component; the mixed powder is put into a special forming mold for the thermal insulation component, and a 100T hydraulic press is used to apply a pressure of 100MPa, and the hydraulic press model is: YT-100S-00, to die-cast the mixed powder into the thermal insulation component.

[0092] Example 3

[0093] The preparation method of the integrated tray heat insulation component is as follows:

[0094] The raw materials are formulated as follows by weight percentage:

[0095] (1). Nano silicon dioxide 70%;

[0096] (2). Pseudo-boehmite 10%;

[0097] (3). High silica chopped fibers 3%;

[0098] (4). Rutile titanium dioxide 4%;

[0099] (5). Magnesium aluminum silicate powder 13%;

[0100] Nano-silica, pseudo-boehmite, high-silica chopped fibers, rutile titanium dioxide, and magnesium aluminum silicate powder are weighed according to the formula ratio and added into a mixer in sequence, and stirred evenly at room temperature for 10 minutes to obtain the final mixed powder to be formed for the thermal insulation component; the mixed powder is put into a special forming mold for the thermal insulation component, and a 100T hydraulic press is used to apply a pressure of 100MPa, and the hydraulic press model is: YT-100S-00, to die-cast the mixed powder into the thermal insulation component.

[0101] Example 4

[0102] The preparation method of the integrated tray heat insulation component is as follows:

[0103] The raw materials are formulated as follows by weight percentage:

[0104] (1). Nano silicon dioxide 50%;

[0105] (2). Pseudo-boehmite 15%;

[0106] (3). High silica chopped fibers 5%;

[0107] (4). Rutile titanium dioxide 5%;

[0108] (5). Magnesium aluminum silicate powder 15%;

[0109] (6) Thermal insulation materials 10%;

[0110] The preparation method of the thermal insulation material is as follows:

[0111] S1, placing 0.4 kg of carbon aerogel in a vacuum dryer, and adding 0.5 kg of triacetoxyvinylsilane and 0.8 kg of 1 mol / L sodium hydroxide aqueous solution into the vacuum dryer, respectively, sealing and evacuating; placing the vacuum dryer in an insulated box at 170° C. for 8 hours to obtain a pretreated carbon aerogel;

[0112] S2, mixing 10 kg of silicone sol, 6 kg of water and 4 kg of anhydrous ethanol and stirring for 2 hours, wherein the silicone sol is composed of vinyl trimethoxy silane and methacryloxypropyl methyl diethoxy silane in a mass ratio of 1:1; preparing polysiloxane sol;

[0113] S3, the pretreated carbon aerogel prepared in step S1 and 0.2 kg of alumina fiber are uniformly dispersed in the polysiloxane sol prepared in step S2, stirred at 20 rpm at 70°C for 3 hours, then heated to 80°C and kept warm for 6 hours; heated to 1200°C in a nitrogen atmosphere, kept warm for 4 hours, and cooled to room temperature with the furnace to obtain a composite material;

[0114] S4. Place the composite material obtained in step S3 in a tube furnace, heat it to 600° C. in an air environment, and keep it warm for 5 hours. Then place it in a vacuum dryer, treat it with 0.5 kg of 1,8-bis(trichlorosilylethyl)hexafluorooctane at 70° C. for 3 hours, and then dry it to obtain a thermal insulation material.

[0115] Nano-silica, pseudo-boehmite, high-silica chopped fibers, rutile titanium dioxide, magnesium aluminum silicate powder, and thermal insulation materials are weighed according to the formula ratio and added into a mixer in sequence, and stirred evenly at room temperature for 10 minutes to obtain a final mixed powder to be formed for the thermal insulation component; the mixed powder is put into a special forming mold for the thermal insulation component, and a 100T hydraulic press is used to apply a pressure of 100MPa, and the hydraulic press model is: YT-100S-00, to die-cast the mixed powder into the thermal insulation component.

[0116] Example 5

[0117] The preparation method of the integrated tray heat-insulating component is basically the same as that of Example 4, the only difference being the difference in the heat-insulating material.

[0118] The preparation method of the thermal insulation material is as follows:

[0119] S1, placing 0.4 kg of carbon aerogel in a vacuum dryer, and adding 0.5 kg of tetraethyl orthosilicate and 0.8 kg of 1 mol / L sodium hydroxide aqueous solution into the vacuum dryer, respectively, sealing and evacuating; placing the vacuum dryer in an insulated box at 170° C. for 8 hours to obtain a pretreated carbon aerogel;

[0120] S2, mixing 10 kg of silicone sol, 6 kg of water and 4 kg of anhydrous ethanol and stirring for 2 hours, wherein the silicone sol is composed of vinyl trimethoxy silane and methacryloxypropyl methyl diethoxy silane in a mass ratio of 1:1; preparing polysiloxane sol;

[0121] S3, the pretreated carbon aerogel prepared in step S1 and 0.2 kg of alumina fiber are uniformly dispersed in the polysiloxane sol prepared in step S2, stirred at 20 rpm at 70°C for 3 hours, then heated to 80°C and kept warm for 6 hours; heated to 1200°C in a nitrogen atmosphere, kept warm for 4 hours, and cooled to room temperature with the furnace to obtain a composite material;

[0122] S4. Place the composite material obtained in step S3 in a tube furnace, heat it to 600° C. in an air environment, and keep it warm for 5 hours. Then place it in a vacuum dryer, treat it with 0.5 kg of 1,8-bis(trichlorosilylethyl)hexafluorooctane at 70° C. for 3 hours, and then dry it to obtain a thermal insulation material.

[0123] Example 6

[0124] The preparation method of the integrated tray heat-insulating component is basically the same as that of Example 4, the only difference being the difference in the heat-insulating material.

[0125] The preparation method of the thermal insulation material is as follows:

[0126] S1, placing 0.4 kg of carbon aerogel in a vacuum dryer, and adding 0.5 kg of triacetoxyvinylsilane and 0.8 kg of 1 mol / L sodium hydroxide aqueous solution into the vacuum dryer, respectively, sealing and evacuating; placing the vacuum dryer in an insulated box at 170° C. for 8 hours to obtain a pretreated carbon aerogel;

[0127] S2, mixing 10 kg of silicone sol, 6 kg of water and 4 kg of anhydrous ethanol and stirring for 2 hours, wherein the silicone sol is composed of methyltrimethoxysilane and methacryloxypropylmethyldiethoxysilane in a mass ratio of 1:1; preparing polysiloxane sol;

[0128] S3, the pretreated carbon aerogel prepared in step S1 and 0.2 kg of alumina fiber are uniformly dispersed in the polysiloxane sol prepared in step S2, stirred at 20 rpm at 70°C for 3 hours, then heated to 80°C and kept warm for 6 hours; heated to 1200°C in a nitrogen atmosphere, kept warm for 4 hours, and cooled to room temperature with the furnace to obtain a composite material;

[0129] S4. Place the composite material obtained in step S3 in a tube furnace, heat it to 600° C. in an air environment, and keep it warm for 5 hours. Then place it in a vacuum dryer, treat it with 0.5 kg of 1,8-bis(trichlorosilylethyl)hexafluorooctane at 70° C. for 3 hours, and then dry it to obtain a thermal insulation material.

[0130] Example 7

[0131] The preparation method of the integrated tray heat-insulating component is basically the same as that of Example 4, the only difference being the difference in the heat-insulating material.

[0132] The preparation method of the thermal insulation material is as follows:

[0133] S1, placing 0.4 kg of carbon aerogel in a vacuum dryer, and adding 0.5 kg of triacetoxyvinylsilane and 0.8 kg of 1 mol / L sodium hydroxide aqueous solution into the vacuum dryer, respectively, sealing and evacuating; placing the vacuum dryer in an insulated box at 170° C. for 8 hours to obtain a pretreated carbon aerogel;

[0134] S2, mixing 10 kg of silicone sol, 6 kg of water and 4 kg of anhydrous ethanol and stirring for 2 hours, wherein the silicone sol is composed of vinyltrimethoxysilane and dimethyldimethoxysilane in a mass ratio of 1:1; preparing polysiloxane sol;

[0135] S3, the pretreated carbon aerogel prepared in step S1 and 0.2 kg of alumina fiber are uniformly dispersed in the polysiloxane sol prepared in step S2, stirred at 20 rpm at 70°C for 3 hours, then heated to 80°C and kept warm for 6 hours; heated to 1200°C in a nitrogen atmosphere, kept warm for 4 hours, and cooled to room temperature with the furnace to obtain a composite material;

[0136] S4. Place the composite material obtained in step S3 in a tube furnace, heat it to 600° C. in an air environment, and keep it warm for 5 hours. Then place it in a vacuum dryer, treat it with 0.5 kg of 1,8-bis(trichlorosilylethyl)hexafluorooctane at 70° C. for 3 hours, and then dry it to obtain a thermal insulation material.

[0137] Comparative Example 1

[0138] The preparation method of the integrated tray heat-insulating component is basically the same as that of Example 4, the only difference being the difference in the heat-insulating material.

[0139] The preparation method of the thermal insulation material is as follows:

[0140] S1, placing 0.4 kg of carbon aerogel in a vacuum dryer, and adding 0.5 kg of triacetoxyvinylsilane and 0.8 kg of 1 mol / L sodium hydroxide aqueous solution into the vacuum dryer, respectively, sealing and evacuating; placing the vacuum dryer in an insulated box at 170° C. for 8 hours to obtain a pretreated carbon aerogel;

[0141] S2, mixing 10 kg of siloxane sol, 6 kg of water and 4 kg of anhydrous ethanol and stirring for 2 hours, wherein the siloxane sol is vinyltrimethoxysilane; preparing polysiloxane sol;

[0142] S3, the pretreated carbon aerogel prepared in step S1 and 0.2 kg of alumina fiber are uniformly dispersed in the polysiloxane sol prepared in step S2, stirred at 20 rpm at 70°C for 3 hours, then heated to 80°C and kept warm for 6 hours; heated to 1200°C in a nitrogen atmosphere, kept warm for 4 hours, and cooled to room temperature with the furnace to obtain a composite material;

[0143] S4. Place the composite material obtained in step S3 in a tube furnace, heat it to 600° C. in an air environment, and keep it warm for 5 hours. Then place it in a vacuum dryer, treat it with 0.5 kg of 1,8-bis(trichlorosilylethyl)hexafluorooctane at 70° C. for 3 hours, and then dry it to obtain a thermal insulation material.

[0144] Comparative Example 2

[0145] The preparation method of the integrated tray heat-insulating component is basically the same as that of Example 4, the only difference being the difference in the heat-insulating material.

[0146] The preparation method of the thermal insulation material is as follows:

[0147] S1, placing 0.4 kg of carbon aerogel in a vacuum dryer, and adding 0.5 kg of triacetoxyvinylsilane and 0.8 kg of 1 mol / L sodium hydroxide aqueous solution into the vacuum dryer, respectively, sealing and evacuating; placing the vacuum dryer in an insulated box at 170° C. for 8 hours to obtain a pretreated carbon aerogel;

[0148] S2, mixing 10 kg of silicone sol, 6 kg of water and 4 kg of anhydrous ethanol and stirring for 2 hours, wherein the silicone sol is methacryloxypropylmethyldiethoxysilane; preparing polysiloxane sol;

[0149] S3, the pretreated carbon aerogel prepared in step S1 and 0.2 kg of alumina fiber are uniformly dispersed in the polysiloxane sol prepared in step S2, stirred at 20 rpm at 70°C for 3 hours, then heated to 80°C and kept warm for 6 hours; heated to 1200°C in a nitrogen atmosphere, kept warm for 4 hours, and cooled to room temperature with the furnace to obtain a composite material;

[0150] S4. Place the composite material obtained in step S3 in a tube furnace, heat it to 600° C. in an air environment, and keep it warm for 5 hours. Then place it in a vacuum dryer, treat it with 0.5 kg of 1,8-bis(trichlorosilylethyl)hexafluorooctane at 70° C. for 3 hours, and then dry it to obtain a thermal insulation material.

[0151] Comparative Example 3

[0152] The preparation method of the integrated tray heat-insulating component is basically the same as that of Example 4, the only difference being the difference in the heat-insulating material.

[0153] The preparation method of the thermal insulation material is as follows:

[0154] S1, mixing 10 kg of silicone sol, 6 kg of water and 4 kg of anhydrous ethanol and stirring for 2 hours, wherein the silicone sol is composed of vinyl trimethoxy silane and methacryloxypropyl methyl diethoxy silane in a mass ratio of 1:1; preparing polysiloxane sol;

[0155] S2, 0.2 kg of alumina fiber was uniformly dispersed in the polysiloxane sol prepared in step S1, stirred at 20 rpm at 70°C for 3 hours, then heated to 80°C and kept warm for 6 hours; heated to 1200°C in a nitrogen atmosphere, kept warm for 4 hours, and cooled to room temperature with the furnace to obtain a composite material;

[0156] S3. Place the composite material obtained in step S2 in a tube furnace, heat it to 600° C. in an air environment, and keep it warm for 5 hours. Then place it in a vacuum dryer, treat it with 0.5 kg of 1,8-bis(trichlorosilylethyl)hexafluorooctane at 70° C. for 3 hours, and then dry it to obtain a thermal insulation material.

[0157] Test Example 1

[0158] Thermal insulation test

[0159] Place the finished heating plate composed of heat-insulating components produced according to the formula into the test housing, and place a thermocouple probe at 5mm from the bottom of the heating plate and 5mm from the side of the heating plate at the 12 o'clock position on the front of the heating plate. At the same time, control the temperature in the furnace at 700±10℃, power on and test for 60 minutes, and record the average temperature value of each test position at the 60th minute;

[0160] The test results are shown in Table 1.

[0161] Table 1

[0162]

[0163] Test Example 2

[0164] Energy efficiency test

[0165] Tested according to European standard EN60350-2;

[0166] The test results are shown in Table 2.

[0167] Table 2

[0168] Experimental protocol Energy efficiency <195Wh / kg Example 1 188.2 Example 2 186.0 Example 3 187.3 Example 4 180.5 Example 5 183.5 Example 6 183.7 Example 7 183.0 Comparative Example 1 182.6 Comparative Example 2 182.9 Comparative Example 3 183.6 Commercially available split tray A 188.9 Commercially available split tray B 199.3 Commercially available split tray C 195.8

[0169] Test Example 3

[0170] Withstand voltage test

[0171] The heat insulating components of Examples 4-7 and Comparative Examples 1-3 were made into furnace plates and placed in a constant temperature and humidity chamber at 93% and 25°C for 48 hours, then taken out and placed for another 2 hours before testing their withstand voltage insulation performance. The test results are shown in Table 3.

[0172] Table 3

[0173] Experimental protocol Withstand voltage (2000V, 3S, 5mA) Example 4 1.20mA Example 5 1.26mA Example 6 1.27mA Example 7 1.29mA Comparative Example 1 1.24mA Comparative Example 2 1.23mA Comparative Example 3 1.19mA Commercially available split tray A 2.20mA Commercially available split tray B 5.85mA Commercially available split tray C 6.60mA

[0174] Test Example 4

[0175] Drop test

[0176] The finished heating plate is placed at a height of 200mm, and is freely dropped vertically with the front side facing downward for 3 cycles. The heat insulation components of the heating plate are not scattered, there are no through cracks and there are ≤2 cracks, and the heating wire has no wire jumping phenomenon. The test results are shown in Table 4.

[0177] Table 4

[0178] Experimental protocol Drop test: no heat insulation parts scattered, ≤2 cracks, no wire jump phenomenon of heating wire Example 1 No cracking, scattering, or wire skipping Example 2 No cracking, scattering, or wire skipping Example 3 No cracking, scattering, or wire skipping Example 4 No cracking, scattering, or wire skipping Example 5 No cracking, scattering, or wire skipping Example 6 No cracking, scattering, or wire skipping Example 7 No cracking, scattering, or wire skipping Comparative Example 1 No cracking, scattering, or wire skipping Comparative Example 2 No cracking, scattering, or wire skipping Comparative Example 3 No cracking, scattering, or wire skipping Commercially available split tray A The heat insulation ring has a slight crack, scattering, and wire jumping phenomenon Commercially available split tray B There is a through crack in the heat insulation ring Commercially available split tray C There are 2 cracks in the heat insulation ring, and the wire is slightly broken

[0179] It can be seen from the data in Tables 1-4 that the thermal insulation, energy efficiency, insulation and strength performance test results of the integrated plate thermal insulation component prepared in Example 4 are the best.

[0180] Among them, the integrated disc heat insulation component prepared by the embodiment of the present invention performs better than the split disc. The main reason lies in its innovative structural design and special material formula. The integrated disc heat insulation component adopts the method of integral press molding, which effectively avoids the problem of heat overflow from the joint of the ring and gasket, reduces the extra heat loss, and improves the efficiency of thermal energy utilization. In addition, the formulation technology of this component selects materials such as nano-silica, high-purity pseudo-boehmite, high-silica chopped fibers, rutile titanium dioxide and magnesium aluminum silicate powder. These materials have excellent thermal insulation, insulation and mechanical strength properties, making the integrated disc heat insulation component perform better in terms of temperature insulation, energy efficiency, insulation and structural strength. At the same time, this one-piece molding design also helps to simplify the production process, reduce costs and improve production efficiency.

[0181] The integrated tray insulation component prepared in Example 2 performs better than Examples 1 and 3 due to its unique material ratio. In Example 2, the content of nano-silicon dioxide is increased to 60%, which increases the thermal insulation performance of the insulation component because nano-silicon dioxide has high porosity and low thermal conductivity and can effectively block heat transfer. At the same time, the proportion of magnesium aluminum silicate powder in Example 2 is reduced to 15%. This material usually has good mechanical properties, but a higher proportion may increase thermal conductivity, so a proper reduction in its proportion helps to improve thermal insulation performance. In addition, high-silica chopped fibers account for 5%, which provides a certain structural strength for the insulation component without significantly increasing density or thermal conductivity. Although the proportion of rutile titanium dioxide remains unchanged, its high refractive index and high temperature resistance help to improve the temperature resistance and thermal shock resistance of the component. Combining these adjustments, the formula of Example 2 may achieve the best balance of thermal insulation performance, mechanical strength and temperature resistance.

[0182] Compared with Example 5, Example 4 performs better in performance tests such as thermal insulation, energy efficiency and structural strength. The main reason is that triacetoxyvinylsilane is used in the preparation process of its thermal insulation material. Triacetoxyvinylsilane contains carbon-carbon double bonds, which enables it to form a more stable three-dimensional network structure and increase the amount of triacetoxyvinylsilane attached to the carbon aerogel, which helps to maintain the physical and chemical properties of the thermal insulation material in high-temperature application environments, thereby showing a more excellent thermal insulation effect and longer service life in practical applications. Therefore, the use of triacetoxyvinylsilane brings better comprehensive performance to the thermal insulation material, making it perform better in the application of integrated tray thermal insulation components.

[0183] The silicone sol used in Example 4 is composed of vinyltrimethoxysilane and methacryloxypropylmethyldiethoxysilane in a mass ratio of 1:1. This combination gives the integrated tray insulation component better performance. The carbon-carbon double bonds of vinyltrimethoxysilane enable it to provide good thermal stability and mechanical properties through the cross-linked network of the polymer, while the carbon-carbon double bonds in methacryloxypropylmethyldiethoxysilane help to form a tough and well-adhesive polymer matrix. The synergistic effect of these two silicone sols not only enhances the structural strength of the thermal insulation material, but also improves the temperature resistance and thermal insulation performance of the thermal insulation material by promoting more chemical cross-linking points. In addition, this combination may also improve the structure of the thermal insulation material and further reduce the thermal conductivity, thereby showing better comprehensive performance in terms of thermal insulation, energy efficiency and structural strength.

Claims

1. A method for preparing an integrated heat-insulating component, characterized in that: The following raw materials are die-casted, and the weight percentage of each raw material is as follows: (1). Nano silicon dioxide 30-60%; (2). Pseudo-boehmite 5-25%; (3). High silica chopped fibers 1-10%; (4). Titanium dioxide 3-15%; (5). Magnesium aluminum silicate powder 5-20%; (6) Thermal insulation materials 1-10%; The preparation method of the thermal insulation material is as follows, in parts by weight: S1, placing 0.3-0.5 parts of carbon aerogel in a vacuum dryer, and adding 0.4-0.6 parts of triacetoxyvinylsilane and 0.7-0.9 parts of 0.5-2 mol / L sodium hydroxide aqueous solution in the vacuum dryer, respectively, sealing and evacuating; placing the vacuum dryer in an insulated box at 160-180° C. for 5-10 hours to obtain pretreated carbon aerogel; S2, mixing 8-12 parts of silicone sol, 5-7 parts of water and 3-5 parts of anhydrous ethanol and stirring for 1-3 hours to prepare polysiloxane sol; S3, uniformly dispersing the pretreated carbon aerogel prepared in step S1 and 0.1-0.3 parts of alumina fiber in the polysiloxane sol prepared in step S2, stirring at 10-30 rpm at 60-80°C for 1-5 hours, then heating to 70-90°C, and heat preservation for 4-8 hours; heating to 1000-1500°C in a nitrogen atmosphere, heat preservation for 2-6 hours, and cooling to room temperature with the furnace to obtain a composite material; S4, placing the composite material obtained in step S3 in a tube furnace, heating it to 500-700° C. in an air environment, and heat-treating it for 4-6 hours, then placing it in a vacuum dryer, treating it with 0.4-0.6 parts of 1,8-bis(trichlorosilylethyl)hexafluorooctane at 60-80° C. for 1-5 hours, and then drying it to obtain a thermal insulation material; The siloxane sol is composed of vinyl trimethoxy silane and methacryloxypropyl methyl diethoxy silane in a mass ratio of 0.5-2:0.5-2.

2. The method for preparing the integrated heat-insulating component according to claim 1, characterized in that: The specific surface area of ​​the nano-silicon dioxide is 80-120 m 2 / g; the particle size of pseudo-boehmite is ≤50μm; the diameter of high-silica chopped fibers is 5-8μm, and the length is between 6±2mm; the titanium dioxide is rutile titanium dioxide, and the particle size of rutile titanium dioxide is 180-220μm; the mesh number of magnesium aluminum silicate powder is 1100-1300 mesh.

3. The method for preparing the integrated heat-insulating component according to claim 1, characterized in that: The preparation method of the integrated disc thermal insulation component is as follows: nano-silicon dioxide, pseudo-boehmite, high-silica chopped fibers, titanium dioxide, magnesium aluminum silicate powder, and thermal insulation materials are weighed according to the formula ratio and added into a mixer in sequence, and stirred evenly at room temperature for 5-15 minutes to obtain a final mixed powder to be formed for the thermal insulation component; the mixed powder is put into a special forming mold for the thermal insulation component, and the mixed powder is die-cast into the thermal insulation component.

4. The method for preparing the integrated heat-insulating component according to claim 3, characterized in that: The die casting uses an 80T-250T hydraulic press to apply a pressure of 20MPa-120MPa, and the mixed powder is die-cast into a heat insulation component within a time range of 1-10s.

5. An integrated heat-insulating component, characterized in that: The integrated plate heat-insulating component is prepared by the preparation method of any one of claims 1 to 4.

6. The use of the integrated heat-insulating component according to claim 5, characterized in that: Used for the integrated heating plate of electric ceramic stove.

Citation Information

Patent Citations

  • Mullite micro-nano pore heat insulation refractory material and preparation method thereof

    CN114133258A

  • Thermal-insulating material composition and thermal-insulating pad and preparation method thereof and electric cooking appliance

    CN108383544A

  • Surface modified silicon dioxide particles

    EP2110414A1